Evaluation of the relation between cardiac biomarkers and thorax computerized tomography findings in COVID-19 patients - ÖZBEN SADIÇ, BESTE; TİGEN, MUSTAFA KÜRŞAT (FUTURE MEDICINE LTD, 2021)
Background: Troponin levels may be elevated in COVID-19 infection. The aim of this study was to the explore relation between troponin levels and COVID-19 severity. Materials & methods/Results: One hundred and forty consecutive patients with COVID-19 pneumonia were included. Diagnosis of COVID-19 pneumonia was based on positive chest computed tomography (CT) findings. Quantitative PCR test was performed in all patients. Only 74 patients were quantitative PCR-positive. Twenty four patients had severe CT findings and 27 patients had progressive disease. These patients had significantly lower albumin and higher ferritin, D-dimer, lactate dehydrogenase, C-reactive protein, and high-sensitivity cardiac troponin I (hs-cTnI). Conclusion: COVID-19 patients with severe CT findings and progressive disease had higher hs-cTnI levels suggesting the use of hs-cTnI in risk stratification.
Keywords: cardiac biomarkers; COVID-19; myocardial injury; thorax CT; troponin; INFECTION